Dynamics of Lava Flows - Tjondro Indrasutanto (Magister Scientiae, 2009)
Extensive lava flows, like those of Mount Merapi of Central Java, require thickness only of the order of meters and temperatures only slightly above the melting point to spread over distance of the order of hundreds of meters. Other things being equal the spreading distance is propotional to the cube of the thickness of the flow.